Mass Murder in America: Trends, Characteristics, Explanations, and Policy Response - Fox, James Alan (Homicide studies, 2022)
Mass murder, especially involving a firearm, has been a subject of increasing interest among criminologists over the past decade. Lacking an existing and reliable data resource for studying these crimes, several organizations have launched their own database initiatives with, unfortunately, little consensus on definition. As a result, there is confusion regarding the nature and trends of such events. In this paper, we rely on the Associated Press/USA Today/Northeastern University Mass Killing Database, which provides the widest coverage of incidents in the U.S. with four or more victim fatalities, regardless of location, situation, or weapon. First, we present trends in incidents and victimization of mass killings from 2006 through 2020, followed by an examination of various incident, offender, and victim characteristics, distinguishing among the major subtypes. Next, we detail a motivational typology of mass murder and identify the common contributing factors. Finally, we consider the potential effects of certain policy responses related to media coverage, mental health services, and gun restrictions on the prevalence of mass killing.